Alanyl-glutamine Protects Against Damage Induced by Enteroaggregative Escherichia coli Strains in Intestinal Cells. Issue 2 (February 2019) - Prata, Mara M.G.; Cavalcante, Paloma A.; da Silva, Antonio V. Alves; de Medeiros, Pedro H.Q.S.; de Assis Júnior, Eudmar M.; Reyes, Mayra A.V.; Quetz, Josiane da S.; Clementino, Marco A.F.; Ribeiro, Samilly A.; Lima, Ila F.N.; Lima-Junior, Roberto C.P.; Havt, Alexandre; et al.
ABSTRACT: Background: Enteroaggregative Escherichia coli (EAEC) is an important pathogen causing enteric infections worldwide. This pathotype is linked to malnutrition in children from developing countries. Alanyl-glutamine (Ala-Gln) is an immune modulator nutrient that acts during intestinal damage and/or inflammation. This study investigated the effect of EAEC infection and Ala-Gln on cell viability, cell death, and inflammation of intestinal epithelium cells (IEC-6). Methods: Cells were infected with an EAEC prototype 042 strain, an EAEC wild-type strain isolated from a Brazilian malnourished child, and a commensal E coli HS. Gene transcription and protein levels of caspases-3, -8, and -9 and cytokine-induced neutrophil chemoattractant 1 (CINC-1/CXCL1) were evaluated using RT-qPCR, western blot analysis, and ELISA. Results: Infections with both EAEC strains decreased cell viability and induced apoptosis and necrosis after 24 hours. Ala-Gln supplementation increased cell proliferation and reduced cell death in infected cells. Likewise, EAEC strain 042 significantly increased the transcript levels of caspases-3, -8, and -9 when compared to the control group, and Ala-Gln treatment reversed this effect. Furthermore, EAEC induced CXCL1 protein levels, which were also reduced by Ala-Gln supplementation. Conclusion: These findings suggest that EAEC infection promotes apoptosis, necrosis, and intestinal inflammation with involvement of caspases. Supplementation of Ala-Gln inhibits cell death, increases cell proliferation, attenuates mediators associated with cell death, and inflammatory pathways in infected cells. Abstract : Supplemental Digital Content is available in the text